PELAKSANAAN ODR DI INDONESIA SEBAGAI PENYELESAIAN SENGKETA EKONOMI SYARIAH : STAIN Mandailing Natal - Resi Atna Sari (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2020)
Abstract The existence of ODR in Indonesia is still relatively new, so juridically, the use of an online dispute resolution mechanism (ODR) has not been clearly regulated and formulated in the laws and regulations. Considering that these electronic transactions continue to increase, it is necessary to have a legal umbrella to regulate them. Research on the implementation of ODR in Indonesia as a sharia economic dispute settlement is a type of normative legal research, the nature of this research is analytical descriptive. The analysis used in this study is a qualitative method. The arbitration agreement clause contained in the online agreement and the exchange of e-mails is not clearly regulated in Law No.30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The decision from ODR if you want to be registered at the District Court has not been explicitly regulated in Law No.30 of 1999. Among the successes in using ODR are efforts made by companies to consumers (business to consumer) and resolution of disputes regarding domain names (domain name). on the Internet. This system is an example and a successful ODR system although in its development there were a few obstacles due to legal and technical problems.